2021
DOI: 10.3390/ijerph18073358
|View full text |Cite
|
Sign up to set email alerts
|

Burnout Determinants among Nurses Working in Palliative Care during the Coronavirus Disease 2019 Pandemic

Abstract: Nurses working in palliative care are at risk of burnout. The Copenhagen Burnout Inventory was used to determine burnout levels of nurses working in the Portuguese national network of palliative care. We evaluated the contribution of personal, work, and COVID-19 variables in three burnout subclasses: personal, work, and patient-related. A cross-sectional, exploratory, and quantitative design was employed and participants were sampled using convenience and snowball technique. An online survey was conducted and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 39 publications
(30 reference statements)
1
25
0
Order By: Relevance
“…Studies that explored HCPs during the second and third waves reveal no abatement of psychological burden or burnout in HCPs ( Gonçalves et al 2021 ; Nishimura et al 2021a , 2021b ; Tan et al 2020 ). There is growing concern that the protracted crisis may cause lasting harm to HCPs and the health system ( Greenberg and Raferty 2021 ; Lorente et al 2021 ).…”
Section: Introductionmentioning
confidence: 96%
“…Studies that explored HCPs during the second and third waves reveal no abatement of psychological burden or burnout in HCPs ( Gonçalves et al 2021 ; Nishimura et al 2021a , 2021b ; Tan et al 2020 ). There is growing concern that the protracted crisis may cause lasting harm to HCPs and the health system ( Greenberg and Raferty 2021 ; Lorente et al 2021 ).…”
Section: Introductionmentioning
confidence: 96%
“…The Self-fulfillment subscale, which assesses feelings of self-efficacy and self-fulfillment at work. It is composed of 8 items (4,7,9,12,17,18,19,21) and a maximum score of 48. The items were answered by workers using a Likert-type frequency scale ranging from zero "0" (Never) to "6" (Daily) [22].…”
Section: Instrumentmentioning
confidence: 99%
“…Shoja [ 17 ] found that the levels of job stress and burnout in the group of nurses who were exposed to COVID-19 patients were higher than in the group of nurses who did not work with exposure to COVID-19 patients. However, there is insufficient evidence to determine the prevalence of burnout among different specialised care services during the pandemic [ 18 ]. Therefore, the aim of this research was to analyse the levels of burnout in specialised care nurses during the COVID-19 pandemic in relation to a series of socio-demographic and work context variables.…”
Section: Introductionmentioning
confidence: 99%
“…The psychological consequences for the parties involved (healthcare professionals and patients) have not been long in coming. Even before the current pandemic, PC services have always registered higher mortality rates, which per se increase the risk of burnout among healthcare professionals, especially among nurses, due to their particularly close relationship with the patient [14]. Büntzel et al state that, according to doctors, over 70% of cancer patients felt insecure, and up to 21% felt afraid and isolated [15].…”
Section: Introductionmentioning
confidence: 99%